ANALISIS YURIDIS PUTUSAN NOMOR 23-K/PM.III-12/AD/II/2020 TENTANG HOMOSEKSUAL PADA ANGGOTA TNI DITINJAU DALAM HAK ASASI MANUSIA - Wijaya, Alviano Boyko; Yeksi Anakotta, Marthsian (Universitas Ekasakti, 2022)
The purpose of the text is to examine the issue of homosexual act committed by by TNI member from a human rights perspective. The research used is doctrinal legal research. The results of this study can be concluded that homosexsual act commited by TNI member is contrary to article 281 paragraph (1) of the KUHP. In additiaon especially in TNI internal regulations include the telegram of the TNI commander number ST/398/2009 Jo. ST/1648/2019 as emphasized in the supreme court circular letter number 10 of 2020. Homosexsual act also contarty with the human rights in Indonesian as stated in article 28 J paragraph (2) of the UUD 1945 Jo. Article 70 UU HAM. The limitations on the application of human rights that apply in Indonesia are based on considerations of moralitry, security and public policy in a democratic society, so that homosexsual act coomited by TNI members is a contrary toi the provisions of the law that are upheld so that actions coomited by TNI member must be dealt with firmly. Keywords: Homosexsual, TNI Member, Human Rights.